Expected Returns in Treasury Bonds - Cieslak, Anna; Povala, Pavol (Review of Financial Studies, 2015)
We study risk premium in U.S. Treasury bonds. We decompose Treasury yields into inflation expectations and maturity-specific interest-rate cycles, which we define as variation in yields orthogonal to expected inflation. The short-maturity cycle captures the real short-rate dynamics. Jointly with expected inflation, it comprises the expectations hypothesis (EH) term in the yield curve. Controlling for the EH term, we extract a measure of risk-premium variation from yields. The risk-premium factor forecasts excess bond returns in and out of sample and subsumes the common bond return predictor obtained as a linear combination of forward rates.